1998
DOI: 10.1590/s0004-282x1998000100005
|View full text |Cite
|
Sign up to set email alerts
|

Public awareness and attitudes toward epilepsy in different social segments in Brazil

Abstract: -Purpose: To assess public awareness and attitudes toward epilepsy in Brazilians of different cultural and socioeconomic backgrounds. Background: Several studies have examined public awareness and attitudes toward epilepsy in various countries but there are no equivalent data for Brazil or South America. Material and Methods: We have applied the survey proposed by Caveness and Gallup , with some modifications and adaptations to four groups (I-IV) of subjects: I-105 individuals accompanying patients to the Opht… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
21
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 10 publications
3
21
0
1
Order By: Relevance
“…It has been clearly observed that the level of education infl uences the answers about the disease and leads to less pejorative attitudes to persons with epilepsy, corroborating with other researches designed for similar purposes 4,[6][7][8][9][10][11][13][14][15] . It is inferred that populations with a lower level of education and a lower income probably also have less access to information concerning epilepsy and this contributes to maintaining erroneous concepts about the disease.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…It has been clearly observed that the level of education infl uences the answers about the disease and leads to less pejorative attitudes to persons with epilepsy, corroborating with other researches designed for similar purposes 4,[6][7][8][9][10][11][13][14][15] . It is inferred that populations with a lower level of education and a lower income probably also have less access to information concerning epilepsy and this contributes to maintaining erroneous concepts about the disease.…”
Section: Discussionsupporting
confidence: 79%
“…However, this statement could be wrong due to a possible incapacity of this population to recognize a real seizure. These proportions were also observed in the study of Santos and coworkers 7 , in which the proportion of witnessing a seizure was 34% in the non-university population against 73% in the general population. Another aspect observed is that the young adults (17-30yrs) say they have witnessed more convulsive seizures than older people, a fact observed in other studies 4,11 .…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Some of the questions are theoretical and individuals may answer in a politically correct manner, according to someone else s expectations and not reflecting their own opinions. Despite these limitations, this approach has been used in other reports 12,13 .…”
Section: Discussionmentioning
confidence: 99%